Development of the “Bekal Ku Berkualitas” Leaflet for Nutrition Education Among Parents at PAUD–Kindergarten Dinul Islam, Aceh Besar - Sukma, Srinadila; Arnisam, Arnisam (JAND: Journal of Applied Nutrition and Dietetic, 2025)
Child malnutrition remains a major public health problem worldwide. In Indonesia, the Ministry of Health reported through the Indonesian Nutrition Status Survey (SSGI) that the prevalence of stunting in 2022 reached 21.6%. One contributing factor to poor nutritional status among children is inadequate food provision by parents or caregivers, including daily lunch meals. Nutrition education using appropriate media is one strategy to address this issue. This study aimed to develop a leaflet entitled “Bekal Ku Berkualitas” as a nutrition education medium for parents and caregivers at PAUD–Kindergarten Dinul Islam, Aceh Besar. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The sample consisted of 20 parents or caregivers of children enrolled at PAUD–Kindergarten Dinul Islam, Aceh Besar. Data were collected using questionnaires and analyzed using both qualitative and quantitative methods. Expert validation results showed an average feasibility score of 85.7% from material experts, 81.7% from media experts, and 92.5% from language experts, indicating that the leaflet was highly feasible. The average knowledge score of parents increased from 82.00 before the intervention to 92.25 after the intervention. Statistical analysis revealed a significant difference in knowledge before and after the intervention (p = 0.002). In conclusion, the development of the “Bekal Ku Berkualitas” leaflet as a nutrition education medium effectively improved parents’ knowledge regarding quality food provision for children at PAUD–Kindergarten Dinul Islam, Aceh Besar.